An efficient traceable data sharing scheme in cloud computing for mobile devices. (2018) - Wang, Zhiying; Ye, Jun; Wang, Jianfeng
Owing to the convenience of mobile devices and the advantages of cloud computing, it is a fashion to efficiently share data by mobile devices in cloud computing. However, it might be insecure to upload the plaintext directly to the remote cloud server. In order to solve the problem, the data should be encrypted by a secure encryption scheme. Most existing data sharing schemes in cloud computing are either insecure against collusion attack or suffer from a large computational overhead. In this paper, an efficient data sharing scheme in cloud computing for mobile devices is proposed based on convergent encryption and polynomial reconstruction techniques. Moreover, predecryption is used to further reduce the computation overhead of mobile devices. Finally, we utilise traitor tracing technology to track the users who have leaked private keys for their own benefit. Experimental results indicate that the proposed scheme is extremely suitable for mobile devices.